Constraints on multi-item working memory access: performance costs and retrieval dynamics - Tiferet-Dweck, Chen; Keegan, Abigail; Unger, Kerstin (Frontiers in Psychology, 2025)
To support goal-directed behavior, working memory (WM) must flexibly access relevant information. While the mechanisms underlying single-item WM access are comparatively well-studied, less is known about the principles governing multi-item access. Some studies have suggested that dual-item retrieval can be as efficient as single-item access, but it remains unclear whether this reflects reduced inhibitory demands or truly parallel, cost-free retrieval. In Experiment 1, we manipulated the number of relevant vs. irrelevant items in a pre-and retro-cuing WM task. The rationale was that if reduced inhibitory demands benefit multi-item access, then having fewer irrelevant items to suppress would enhance performance. Instead, we found that selecting two out of three items was slower and less accurate than selecting one, arguing against the idea that diminished inhibition underlies multi-item retrieval efficiency. Experiments 2a and 2b further probed retrieval efficiency using a modified dual-access paradigm that leveraged object repetition benefits. By including a control condition to prevent temporal associations between repeated targets and non-targets, we observed that repetition benefits for each item were additive—consistent with serial or limited parallel retrieval—rather than overadditive, which would be expected under fully parallel, cost-free retrieval. These findings clarify key limitations of multi-item WM, with important implications for complex tasks such as language comprehension, decision-making, and problem solving.